Pengembangan Website Koleksi Buku untuk Income Cafe Atelir Ciremai - Sahara, Siti; Zulfikar, Hendra; Saputra, Dimas Rizki (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Development of the Book Collection Website for Ciremai Atelier Cafe is an effort to utilize digital technology to improve cafes' services and income. In an era where internet use is increasingly widespread, the website becomes crucial for businesses in expanding reach and increasing customer involvement. Through needs analysis, careful website design, and the development of relevant features, this research aims to provide practical solutions to meet users' needs and improve their experience in exploring the collection of cafes. Features such as sophisticated book searches, user reviews, online payment systems, and website barcode integration have become the main focus in strengthening interactions between cafes and customers. The website's main page provides users with a user-friendly experience through attractive and informative designs, while comprehensive book information ensures easy and complete access. In conclusion, this website development offers opportunities to increase the presence of online cafes, expand customer bases, and strengthen relationships with existing customers while bringing more diverse and attractive reading experiences to the public.